ANALISIS KADAR APO-A1 SERUM PADA TIKUS PUTIH STRAIN WISTAR (Rattus novergicus) DISLIPIDEMIA TERHADAP PEMBERIAN EKSTRAK KULIT BUAH APEL [Malus sylvestris Mill] VARIETAS ROOM BEAUTY - Riyadatus Solihah (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2018)
Dyslipidemia is a disorder of lipid metabolism characterized by increased levels of total cholesterol, triglycerides, low density lipoprotein or a decrease in high-density lipoprotein in the blood, while hyperlipidemia is a condition where there are elevated levels of lipids in ie blood triglycerides, kolersterol or both. This state tehadap high risk of cardiovascular disease (CVD).This research uses experimental research design pure (True Experimental) and the study design used was the randomized post test only control group design, sample number 32 strain Wistar rats (RattusnovergicusWistar strain) 3-4 month old male weighing approximately 100-120 grams were divided into 4 groups, consisting of 1 control group were only given a high-fat diet feed for 28 days, and 3 treatment groups were given a high-fat diet feeding and apple skin extract with 3 different doses of 0,52 mg / kg bw , 1,04 mg / kg bw, 1,58mg / kg for 10 days. Data analysis with inferensial analysis include analysis of normality test with Shapiro and its homogeneity analysis with test Levene Test. If normal and homogeneous data, then continued by annova test one way with a level of significance of the test, at variance p=0.05 . the test variance be obtained levels of were significant with Apo A1 obtain p= 0.001, data have p <0.05, which means there is a significant effect of extract of Apple Skin to the increased levels of and Apo A1 in the rat. Apple skin extract contains pectin that activated PPAR α can increase the levels of serum Apo-A1 in circulation which is the main and largest of protein fractions role in cholesterol transport. Keywords: Apple Skin, Apo-A1